ENGLISH TEACHERS' QUESTIONING PRACTICES IN PROMOTING STUDENTS' CRITICAL THINKING ABILITY - Silviya Izza Ulinnuha, - (2019)
Questioning is a fundamental part of teaching that happens in every day classroom. Its benefits have been widely known by many scholars to affect students cognitive process including critical thinking. However, as such interconnection between the two areas is presumed to be prevalently important. The investigation of its process development in Indonesian teachers' questioning practices especially High School level are relatively minor. This research aimed to identify the process of teachers' questioning practices that can promote students' critical thinking. The data were obtained through observation and interview in one of Senior High School in Bandung. The observation was conducted for four times involving two classes and two teachers. Using Watson & Glaser (2010) critical thinking appraisal known as RED and questioning clues of Taxonomy revised version by Anderson & Krathwohl (2001) the data were then elaborated and discussed. The findings revealed that in the process of gaining critical thinking, question types especially high level question employed by the teachers took a common setting to stimulate the process of critical thinking. Further data also showed that content of the questions, context of the question as well as the questioning pattern took the significant roles in promoting students critical thinking. Therefore, preparing such a whole questioning process, including the content, the types and the pattern in responding the students will imply into a good questioning that enhance students' critical thinking.